Design and development of dehusker suitable for fresh arecanut - Asokan, D.; Jesudas, D. Manohar; Kavitha, R.; Senthilkumar, T. (Journal of Plantation Crops, 2014)
Arecanut is primarily cultivated for obtaining kernel from its fruit which is chewed in the tender, ripe or processed from. Manual dehusking of arecanut is a slow and tedious process and needs skilled labour. Frequently, due to lack of skilled labour all the fresh areca nuts could not be dehusked immediately. Hence to overcome this problem, farmers are in need of a dehusker for freshly harvested arecanut. Hence, development of suitable unit for dehusking fresh arecanut was contemplated. The physical and mechanical properties of green arecanut and kernel as well as husk were studied. Similarly the effect of compression on the failure of husk and kernel was studied. The husk failed at 0.28 kN of axial loading and the husk and nut failed at 0.36 kN of radial loading. A prototype model which can be operated either manually or by 1.5 kW electric motor was developed with two different types of blades i.e., saw tooth circumferential blades and longitudinal profiled blades. By manual operation the dehusking efficiency were 42 per cent and 63 per cent, respectively for saw tooth and profiled tooth drums. When the dehusker was operated by electric motor the performance was satisfactory with profiled tooth drum. The dehusking efficiency was 82 per cent, damage to kernel was 18 per cent and the capacity was 48 kg of kernel per hour.